Pathogenic mechanisms and vaccine development for Mycoplasma gallisepticum in chickens - Chen, Jiaxin; Liu, Peng; Chen, Ying (Frontiers in Microbiology, 2026)
Mycoplasma gallisepticum (MG) is a significant avian pathogen responsible for chronic respiratory disease in chickens and infectious sinusitis in turkeys (Meleagris gallopavo). It infects the respiratory tract, leading to chronic inflammation and, in some cases, conditions such as synovitis and arthritis. MG causes substantial economic losses in the poultry industry due to reduced egg production, hatchability, meat quality, and increased mortality. The primary pathogenic mechanism involves immune dysregulation, enabling the bacterium to persist in the host and establish chronic infection. Key virulence factors include adhesins (e.g., GapA, CrmA, pMGA), variable surface lipoproteins (e.g., VlhA), and recently characterized molecules like the TatD nuclease. Current control measures include antibiotics, management adjustments, and vaccination. However, extensive use of broad-spectrum antibiotics like tetracyclines and macrolides has led to increased drug resistance. Although commercial vaccines (live attenuated, inactivated, and newer epitope-based and recombinant designs) are available, they often provide incomplete or inefficient protection. This review summarizes the current understanding of MG pathogenesis, highlights recent advances in vaccine development, and discusses the limitations and future directions for MG control.